High-performance nanobiosensing technologies for future diagnostic needs - Martinez-Banderas, Aldo I.; Malki, Anas; Froehlich, Thomas; Petrich, Wolfgang (Trends in biotechnology, 2025)
Diagnostic sensor technologies lie at the core of the healthcare system and encompass disease screening, detection, and therapy monitoring. In past decades, many nanobiosensor technologies have emerged which rely on diverse principles using electrical, magnetic, mass-based, or photonic signal transduction methods. We provide an overview of recent and emerging nanobiosensing transduction technologies and illustrate the reported quantification capabilities for nucleic acids, proteins, and small molecules. The review assesses and compares their performance, multimodality, and multiplexing capabilities as well as their portability and throughput, among other criteria. In addition, we elaborate on demonstrated as well as envisaged medical applications of nanobiosensors. Finally, fundamental limitations such as the diffusion limit are discussed and opportunities for future research are outlined.
Online veröffentlicht: 18 June 2025, Artikelversion: 3. Dezember 2025
Gesehen am 09.02.2026